2016
DOI: 10.3324/haematol.2016.149815
|View full text |Cite
|
Sign up to set email alerts
|

Distinct global binding patterns of the Wilms tumor gene 1 (WT1) −KTS and +KTS isoforms in leukemic cells

Abstract: T he zinc finger transcription factor Wilms tumor gene 1 (WT1) acts as an oncogene in acute myeloid leukemia. A naturally occurring alternative splice event between zinc fingers three and four, removing or retaining three amino acids (±KTS), is believed to change the DNA binding affinity of WT1, although there are conflicting data regarding the binding affinity and motifs of the different isoforms. Increased expression of the WT1 -KTS isoform at the expense of the WT1 +KTS isoform is associated with poor progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 49 publications
1
23
1
Order By: Relevance
“…While there are reports of the +KTS isoform functioning as a transcription factor [49] in certain cell models, comparative investigation of the two isoforms requires a more holistic cell-based approach. A recent deep sequencing study has revealed distinct global binding patterns for the +KTS and -KTS isoforms [50]. It is shown that even though both isoforms have common gene targets, binding of −KTS is specific to transcription start sites and to enhancers, whereas binding of +KTS is more abundant and is specific to regions within gene bodies.…”
Section: Discussionmentioning
confidence: 99%
“…While there are reports of the +KTS isoform functioning as a transcription factor [49] in certain cell models, comparative investigation of the two isoforms requires a more holistic cell-based approach. A recent deep sequencing study has revealed distinct global binding patterns for the +KTS and -KTS isoforms [50]. It is shown that even though both isoforms have common gene targets, binding of −KTS is specific to transcription start sites and to enhancers, whereas binding of +KTS is more abundant and is specific to regions within gene bodies.…”
Section: Discussionmentioning
confidence: 99%
“…The aminoterminal of WT1 contains defined transcriptional activation, as well as repression, domains. 3,4 The −KTS and the +KTS isoforms in our investigation 102 were more highly expressed than non-bound genes, a correlation which was more pronounced for genes that had peaks both around the TSS and in other regulatory areas. Motamedi et al 99 also found that genes, whose expression was significantly different in metanephric rudiments in WT1 knockout mice embryos as compared to WT1-expressing embryos, predominantly reduced their expression in knockout cells, indicating WT1 as more often an activator in this system also.…”
Section: Activation or Repression Of Target Genesmentioning
confidence: 57%
“…The DNA binding motifs for the 2 WT1 isoforms in our investigation 102 are also not enough alike to cause the isoforms to bind the same locations in the genome. A possible explanation for the almost complete separation of the isoforms found in our analysis is a difference in binding partners which could influence choice of binding sites.…”
Section: Distinct Binding Sites Of the Wt1 −Kts And +Kts Isoformsmentioning
confidence: 81%
See 2 more Smart Citations